080 The impact of a summer school on medical student and foundation doctors attitudes to careers in paediatrics. (December 2018) - Knott, C; King, J; Smith, J; Fertleman, C; Winyard, P; Poisson, J; Sharma, S
Abstract : Introduction: Paediatrics has seen a decline in training applications, with a 27.5% drop over the last three years. The RCPCH has taken action to stem the decline, including the successful #paedsrocks twitter campaign, highlighting a need to focus on the positives of a career in paediatrics; however, careers guidance for medical students and foundation doctors is often difficult to access. Methods: We developed a 3 day Paediatric Summer School together with GOSH clinicians, general paediatricians and ICH academics and educators. The content consisted of speciality experts describing their job and exciting innovations in their field, careers discussions, interactive QI and leadership group-work, and sessions delivered by patients. Following the Summer School, we sent a brief 9 question survey to assess the attendee's views and the impact of the summer school on their career aspirations. Results: 55 medical students and foundation doctors attended the summer school. 23 participants completed a 9-question study survey taken after the summer school. Attendees were asked to score their likelihood of a career in paediatrics on a 5-point Likert scale. The mean score before and after the summer school showed a significant increase – 3.87 vs 4.65. Most respondents felt the summer school sessions hearing about subspecialties and the careers talks made them feel more likely to apply for a career in paediatrics. 39% felt that long working hours were the biggest factor putting them off the speciality. Discussion: There is a need to engage with medical students and foundation doctors in order to foster a positive attitude towards a career in paediatrics, especially in the current climate surrounding paediatrics with many negative perceptions of the speciality. Our summer school has shown this approach appears to have a positive impact on medical students and foundation doctor's wishes to pursue a career in paediatrics.